Optimization Design and Experiment of the Radio Frequency Transmission Utilized in Video Capsule Endoscope - 刘刚 颜国正 朱柄全 徐文铭 (Shanghai jiao tong da xue xue bao, 2016)
In view of fuzzy and unstable images received in video capsule endoscopy, and the poor communication effect, an improved radio frequency （RF） transmission circuit module with low power consumption and helix antenna is designed to improve the performance of video transmission and to extend the working time of the capsule. Simulation and analysis of the circuits and antenna with HFSS12 and ADS2011 software are highlighted. Video capsule endoscope prototypes are made and evaluated to verify the feasibility of the proposed design. In vitro tests and animal experiments show that the results of the antenna tests basically meet the simulation, and the power consumption of RF circuit is 15.9 inV. The video capsule endoscope works well with the receiver with multiple receiving antennas, and the working time is more than 9 h. It can realize the wireless transmission of the video data, and images received are clear and stable in comparison with the previous designs.